Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Hotel Patra Jasa Bali Resort & Villas (Jurnal Ilmiah Pariwisata, 2016)
Performance is working result which has strong correlation with organization strategic goal, consumer satisfaction and it will give contribution on economic. Some factors that affect performance are discipline and work motivation. Based on the data obtained in period of 2014-2015 the employee discipline violation in the Hotel Patra Jasa Bali Resort & Villas was increasing and their performance was descreasing.This study aims to find out the effect of discipline and motivation simultaneously and partially toward employee performance and which variable has dominant affect on employee performance at Hotel Patra Jasa Bali Resort & Villas.Data analysis technique consist of validity test, reliability, multiple linear regresion, Ftest, ttest, correlation and determination. The result shows that discipline and work motivation simultanouesly have significant and positive effect toward employee performance at Hotel Patra Jasa Bali Resort & Villas. Based on Fcalculate (159.410) > Ftable (3.06) by using significant level of 0.05. Discipline (X1) partially has positive and also significant affect toward employee performance (Y) with tcalculate 4.677 > ttable 1.976. Work motivation (X2) partially has positive and significant effect toward performance (Y) with tcalculate 8.823 > ttable 1.976. Base on ttest with significant level 5 %, work motivation gives bigges effect on the performance compare to discipline.